Equity valuation, risk, and investment : a practitioner's roadmap - Stimes, Peter C., 1955- (Wiley finance series., 2008)
Author Peter Stimes's analysis of the investment process has long been inspired by some of the best minds in the world of finance, yet some of the ways in which he approaches this discipline are truly unique. In Equity Valuation, Risk, and Investment, Stimes shares his extensive expertise with you and reveals how practitioners can integrate and apply both the theory and quantitative analysis found in finance to the day-to-day decisions they must make with regard to important investment issues.